The Effects of Dependence on Brazilian Third-Party Logistics Satisfaction - Antonio Carlos Rodrigues; Ricardo Silveira Martins (RAC: Revista de Administração Contemporânea, 2021)
Context: studies argue that similar levels of dependence are essential for supplier satisfaction in buyer-supplier relationships. However, asymmetric relationships can also lead to supplier satisfaction. Objective: this paper investigates the effects of benefit-based dependence (positive motivations for maintaining relationships) between buyer and supplier and supplier satisfaction. Methods: response surface analysis (RSA) was used to test the relationship between third-party logistics (3PL) dependence and satisfaction dimensions in 174 dyads. Results: the results demonstrated that about supplier satisfaction, instead of dependence asymmetry what really matters is the degree of dependence between the parties. The more dependent one part is on the other, usually, the greater the supplier’s satisfaction. In many circumstances, a degree of dependence is acceptable and necessary to access resources and opportunities. Conclusions: the interaction between buyer and supplier dependence and supplier satisfaction is complex. Situations of dependence asymmetry in which the supplier is highly dependent on the buyer may still be satisfactory.